What can claims data tell us about risk factors and survival of patients with hepatocellular carcinoma? Insights from a German population-based study - Becht, Selina; Ben Khaled, Najib; Schrodi, Simone; von Bergwelt-Baildon, Michael; Buggisch, Peter; Crispin, Alexander; Hofmann, Wolf-Peter; Marschall, Ursula; Mayerle, Julia; Mörtl, Bernhard; Orabi, Sami; Philipp, Alexander; et al. (Frontiers in Oncology, 2025)
BackgroundGeographic and temporal variations in the incidence and treatment of chronic viral hepatitis and trends in the development of metabolic and behavioral risk factors result in heterogeneous incidences of hepatocellular carcinoma (HCC). Therefore, national epidemiological information should be evaluated to identify the need for action.MethodsThis retrospective observational study included adult patients with incident HCC (2016-2020). A network analysis was performed to investigate inter-relationships among risk factor diagnoses before HCC. Kaplan-Meier method and Cox proportional hazard model were used to analyze survival.FindingsA total of 2,778 patients were included. Mean age was 71.9 years (SD ±9.7); 69% were male. Most frequently documented risk factor diagnoses were diabetes mellitus (76%), obesity (56%), liver fibrosis/cirrhosis (44%), and alcohol abuse (36%). Hepatitis B and C were documented in 4% and 11% of patients. Behavioral and metabolic risk factors were 1.1-1.9-fold more frequent in men. Diabetes mellitus was the most central risk factor diagnosis co-occurring with other metabolic and behavioral risk factors. Median survival was 8.7 months.InterpretationIn this German cohort, risk factor diagnoses before HCC were multifactorial, with metabolic diseases most frequently co-occurring. Survival after HCC was poor. Controlling metabolic risk factors and surveilling at-risk populations are crucial to mitigating the incidence and improving the survival of HCC patients in Germany. Analyzing claims data enabled efficient and effective generation of epidemiological real-world evidence.